Integrated residual void modelling incorporating water balance, hydrogeological and flood modelling, and geotechnical and geochemical assessments for final closure landform risk reduction - Johnston, L; Hattingh, R (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Gaining insight early in the mine planning phase into the potential safety, stability and environmental risks related to the retention of residual mine voids in a final closure landform provides opportunities for incremental adjustments to the design to minimise and mitigate these risks. Modelling the behaviours of residual voids through multidisciplinary, integrated and iterative studies provides an understanding of risks as well as a more rigorous basis for re-evaluating these risks when changes in the mine plan occur or as additional data becomes available. Retaining voids in final mine closure landforms is common practise globally. However, retention of these residual voids can present a range of risks such as: alteration of the hydrology of a surface water system through excessive water harvesting where voids are connected to the surrounding catchment; voids overtopping and releasing contaminants to the surface water environment; releasing contaminants from the voids to groundwater through interaction between the established lake and groundwater systems; instability of the void and final landform surfaces through floodwater ingress or high-velocity interactions with final landform surfaces such as overburden emplacements; and developing unfavourable water quality within the void lake itself, making the water unsuitable for post-mining uses. Through integrated modelling of the water balance, groundwater, lake levels and flooding — and geotechnical and geochemical assessments of the final residual voids within the studies — potential risks can be identified and described in a consolidated, iterative manner rather than at completion of the studies. This allows adjustments to be made along the way to minimise potential risks while saving time and costs related to redesigning the most suitable closure landform and re-running the entire suite of studies.
Keywords: residual mine void